Recycling of solvent used in a solvent extraction of petroleum hydrocarbons contaminated soil. - Wu, Guozhong; Li, Xingang; Coulon, Frederic; Li, Hong; Lian, Jingyan; Sui, Hong (Elsevier Science B.V., Amsterdam., 2011)
The application of water washing technology for recycling an organic composite solvent consisting of hexane and pentane (4:1; TU-A solvent) was investigated for extracting total petroleum hydrocarbons (TPH) from contaminated soil. The effects of water volume, water temperature, washing time and initial concentration of solvent were evaluated using orthogonal experiments followed by single factor experiments. Our results showed that the water volume was a statistically significant factor influencing greatly the water washing efficiency. Although less important, the other three factors have all increased the efficacy of water washing treatment. Based on a treatment of 20g of contaminated soil with a TPH concentration of 140mgg(-1), optimal conditions were found to be at 40°C, 100mL water, 5min washing time and 660mgg(-1) solvent. Semi-continuous water extraction method showed that the concentration of the composite solvent TU-A was reduced below 15mgg(-1) d.w. soil with a recovery extraction efficiency >97%. This finding suggests that water washing is a promising technology for recycling solvent used in TPH extraction from contaminated soils